2012
DOI: 10.21608/ejarc.2012.215023
|View full text |Cite
|
Sign up to set email alerts
|

DIALLEL ANALYSIS USING HAYMAN METHOD TO STUDY GENETIC ARCHITECTURE OF VEGETATIVE GROWTH IN PEAS (Pisum sativum L.)

Abstract: This study was carried out during (2010/2011) growing season in the Vegetative Field Research,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…However, the estimates of narrow sense heritability were low and valued 27.1% (shellout %), 31.8% (seed yield/plant) and 32.9% (100-seeds weight), hereby selection was difficult and should be delayed to later segregating generations. Also, the broad sense heritability was higher for all characters, the line regression between (W\Vr) cut the head line over the original point for all characters (Esho et al, 2012). According to Patel et al (2017), the number of pods per plant and the number of seeds per plant both showed strong heritabilities together with substantial genetic advance, indicating the primacy of additive gene action in the expression of these traits.…”
Section: Gene Actionmentioning
confidence: 87%
“…However, the estimates of narrow sense heritability were low and valued 27.1% (shellout %), 31.8% (seed yield/plant) and 32.9% (100-seeds weight), hereby selection was difficult and should be delayed to later segregating generations. Also, the broad sense heritability was higher for all characters, the line regression between (W\Vr) cut the head line over the original point for all characters (Esho et al, 2012). According to Patel et al (2017), the number of pods per plant and the number of seeds per plant both showed strong heritabilities together with substantial genetic advance, indicating the primacy of additive gene action in the expression of these traits.…”
Section: Gene Actionmentioning
confidence: 87%
“…The pea seed richs in protein (39.75%) and has mixed carbohydrates, vitamins, minerals, and anti-oxidant ingredients 4 , 5 . Regular consumption of pea in human diet helps health and reduces the risk of cancer 6 .…”
Section: Introductionmentioning
confidence: 99%